Naamah - Blake, Sarah (Poet) (Riverhead Books, 2019)
"Revisits the story of the Ark that rescued life on earth, and rediscovers the agonizing burdens endured by the woman at the heart of the story. Naamah is a parable for our time: a fable of body, spirit, and resilience"--